Occupational therapy in oncology and palliative care - Cooper, Jill, ....- (Chichester : Wiley, 2006)
Now in its second edition, this is the only book on occupational therapy in oncology and palliative care. It has been thoroughly updated, contains new chapters, and like the first edition will appeal to a range of allied health professionals working with patients with a life-threatening illness. The book explores the nature of cancer and challenges faced by occupational therapists in oncology and palliative care. It discusses the range of occupational therapy intervention in symptom control, anxiety management and relaxation, and the management of breathlessness and fatigue. The book is produced in an evidence-based, practical, workbook format with case studies. New chapters on creativity as a psychodynamic approach; outcome measures in occupational therapy in oncology and palliative care; HIV-related cancers and palliative care.
Keywords: Oncologie -- Ergotherapie; Palliatieve zorg -- Ergotherapie